Frantz Fanon's Black skin, white masks : new interdisciplinary essays - Silverman, Maxim (Texts in culture., 2012)
First published in 1952, Frantz Fanon's 'Black Skin, White Masks' is one of the most important anti-colonial works of the post-war period. It is both a profound critique of the conscious and unconcious ways in which colonialism brutalises the colonised and a passionate cry from deep within a black body alienated by the colonial system and in search of liberation from it. This volume is the first collection of essays specifically devoted to Fanon's text. It offers a wide range of interpretations of the text by leading scholars in a number of disciplines. Chapters deal with Fanon's Martinican her.